Feasibility study of cassava meal in broiler diets by partial replacing energy source (corn) in regard to gross response and carcass traits - Hossain, MA; Amin, JR; Hossain, ME (International Journal of Agricultural Research, Innovation and Technology, 2014)
Day-old unsexed broiler chicks (Cobb 500) were used to investigate the growth responses and meat yield traits by nourishing them under four dietary treatment group in inclusion of cassava meal with partial substitution of valuable energy source (maize or corn). A total of 260 birds were assigned randomly into four dietary treatments [T1 (0%); T2 (10%); T3 (20%), and T4 (30%)]; each replicated 5 times, 13 birds/replicate in a completely randomized design. Birds were reared with ad libitum feeding, similar housing, and environmental management condition from d1-35 days. Growth responses of broilers in terms of feed intake, body weight, feed conversion ratio (FCR), livability and meat yield traits were assessed in this study. Except for first week, the feed intake of birds on cassava treated diets up to 21 and 35 days was significantly (p<0.001) higher than the non-cassava or control diet (T1). Feed intake of broilers on cassava treated diet (T4 ) had the highest (2795.8 g/b) while the birds of control (T1) diet group consumed the lowest feed (2771.9 g/b) at 35 day. Live weight decreased (p<0.001) with the inclusion of cassava meal diets up to 21 day only; and live weights up to 7 and 35 days were identical between treatment. FCR up to 21 day was improved (p<0.001) on control diet (T1) and deteriorated on cassava treated diets. FCR values up to 7 and 35 days were unaffected by all the treatment groups. Neither the livability nor the meat yield traits (thigh, breast, drumstick, shank, neck, giblet, wing and dressing yield) of broiler chickens was influenced by the dietary treatments regardless of feeding broiler chickens with cassava or non-cassava diets in this study. It may be deduced based on the present findings that, cassava tuber meal might be a potential ingredient to replace the costly maize up to 300 g kg-1 without affecting growth performance of the broiler chickens. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17846 Int. J. Agril. Res. Innov. & Tech. 3 (2): 59-65, December, 2013